Menulis Teks Pidato Persuasif, Motivasi Belajar, dan Pendekatan Saintifik dengan Bantuan Media Powtoon - Ika Mustika; Alfa Mitri Suhara; Endri Luki Fauzi (Ranah: Jurnal Kajian Bahasa, 2021)
The purpose of this research is to determine the ability to write persuasive speech text and learning motivation of junior high school students whose learning uses a scientific approach assisted by powtoon media compared to those using a scientific approach, to determine whether there is a relationship between learning motivation and the ability to write persuasive speech text of junior high school students, and to Knowing student performance in implementing the scientific approach, solving knowledge questions, and completing practical assignments to write persuasive speech texts. The method used in this study is a quasi-experimental type nonequivalent control group design. The sample in this study were 50 junior high school students. Based on the research data, it was found that the experimental class was better at writing persuasive speech texts than the control class. In the association test data between the ability to write persuasive speech text and learning motivation, it turns out that in the experimental class the Sig value is 0.058> 0.05 and in the control class the sig value is 0.357> 0.05. These results mean that there is no association between the ability to write persuasive speech texts and learning motivation in either the experimental class or the control class. The performance of students when implementing the scientific approach assisted by the powtoon media was 86.66%. These results meant that the student's performance was very good. The student's performance in his ability to write persuasive speech texts in the experimental class was in the good category, while in the control class it was in the poor category. AbstrakTujuan dari penelitian yaitu untuk mengetahui kemampuan menulis teks pidato persuasif dan motivasi belajar siswa SMP yang pembelajarannya menggunakan pendekatan saintifik dengan bantuan media Powtoon dibandingkan dengan yang menggunakan pendekatan saintifik, untuk mengetahui ada tidaknya hubungan antara motivasi belajar dengan kemampuan menulis teks pidato  persuasif siswa SMP, dan untuk mengetahui kinerja siswa dalam implementasi pendekatan saintifik, menyelesaikan soal-soal pengetahuan, dan menyelesaikan tugas praktik menulis teks pidato persuasif. Metode yang digunakan dalam penelitian adalah quasi eksperimen dengan tipe nonequivalent control group design. Sampel pada penelitian ini yaitu siswa SMP yang berjumlah 50 orang. Berdasarkan data penelitian diperoleh hasil bahwa kelas eksperimen lebih baik dalam menulis teks pidato persuasif dibandingkan kelas kontrol. Pada data uji asosiasi antara kemampuan menulis teks pidato persuasif dengan motivasi berlajar ternyata pada kelas eksperimen diperoleh nilai Sig 0,058> 0,05 dan di kelas kontrol diperoleh nilai  Sig 0,357 > 0,05. Hasil tersebut bermakna bahwa tidak ada asosiasi antara kemampuan menulis teks pidato persuasif dan motivasi belajar baik di kelas eksperimen ataupun kelas kontrol. Kinerja siswa pada saat mengimplementasikan pendekatan saintifik dengan bantuan media powtoon diperoleh hasil 86,66 % hasil tersebut bermakna bahwa kinerja siswa sangat baik. Adapun kinerja siswa dalam kemampuannya dalam menulis teks pidato persuasif di kelas eksperimen yaitu ada dalam kategori baik, sedangkan di kelas kontrol yaitu dalam kategori kurang.